A Journey from This World to the Next - Fielding, Henry, 1707-1754 (Salt Lake City, UT : Project Gutenberg, 1997)
"A Journey from This World to the Next" by Henry Fielding is a satirical novel written in the early 18th century. The narrative follows a protagonist who, upon dying, embarks on an allegorical journey to the afterlife, encountering various spirits and interpreting the experiences of life and death through whimsical adventures and philosophical reflections. The opening of the novel introduces the protagonist's death and his immediate meeting with Mercury, who guides him to the stage that leads to the other world. After a humorous escape from his lifeless body, the protagonist learns he must quickly depart for the afterlife. The narrative is rich with whimsical observations about the nature of life and death, as he begins his journey filled with interactions with other spirits, each offering tales of their own deaths and engaging in discussions about the follies of the earthly realm. The tone is light-hearted yet thought-provoking, setting the stage for a deeper exploration of moral and philosophical themes through satire. (This is an automatically generated summary.)
Release date is 1997-12-01
Produced by Charles Keller
Keywords: Supernatural -- Fiction; English fiction; Paranormal fiction